Biopesticides in sustainable agriculture: Current status and prospects - Berlitz, Diouneia Lisiane; Fiuza, Lidia Mariana; Polanczyk, Ricardo Antônio [UNESP]; Ardisson-Araújo, Daniel Mendes Pereira; Cassal, Maximiano Corrêa; Capalbo, Deise Maria Fontana (My University, 2021)
Sustainable agriculture is on the rise in different countries of the world. On the other hand, there is an increase in the demand for food and the production of different cultures, which requires the reduction of agents that impact the environment, such as chemical inputs. This chapter will introduce biopesticides in this challenging scenario: the ones available, their market, and their interaction with chemical pesticides (as coexistence is demanded in the transition for a better production system). Furthermore, an overview will discuss the future research in prospecting for bioproducts, their production issues and potential market as effective protagonists of a sustainable agriculture in Brazil and in the world.